An Exploratory Investigation of the Palatoglossus Muscle in Children Using Magnetic Resonance Imaging. - Power, Samantha; Kotlarek, Katelyn J. (Journal of Speech, Language & Hearing Research, 2022)
Purpose: There is currently little evidence reporting the typical morphology of the palatoglossus (PG) muscle. The primary purpose of this exploratory study is to determine whether magnetic resonance imaging (MRI) methods used to quantify the morphology of the levator veli palatini (LVP) muscle can be applied to the PG. The secondary purpose is to provide preliminary data regarding the relationship between the LVP and PG muscles in children. Method: Ten children between ages of 4 and 7 years participated in this study. Each participant was scanned using a nonsedated, child-friendly protocol with a T2-weighted, three-dimensional anatomical scan to obtain images of the oropharyngeal anatomy. Custom, oblique-coronal image planes were created to visualize and measure the LVP and PG muscles in their entirety from origin to insertion. Thermo Scientific Amira Software was used to obtain 2D measurements of PG muscle length, width, velar insertion distance, lingual insertion distance, and several angle measurements. Results: The PG ranged from 17.95 to 26.96 mm in length across participants. Velar insertion distance ranged from 17.22 to 30.95 mm. Lingual insertion distance ranged from 26.91 to 36.02 mm. Width ranged from 2.32 to 3.08 mm. The angle formed by the PG and LVP muscle planes ranged from 7.3° to 52.7°. The LVP insertion angle ranged from 42.5° to 75.9°. The PG insertion angle ranged from 16.9° to 52.3°. Conclusions: MRI was successful in visualizing the PG muscle. The PG was consistent in size and shape within an individual participant but varied across the participant cohort.